2011
DOI: 10.5897/jyfr11.004
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Spilocaea oleagina, causal agent of olive leaf spot, in North of Iran

Abstract: Olive leaf spot or peacock spot, caused by the fungal pathogen Spilocaea oleagina, can cause reduced growth and yield in olive trees (Olea eurapaea). Investigations were carried out during 2007-2010 to measure the prevalence and severity of olive leaf spot in the northern olive growing regions of Iran. The susceptibility of ten cultivars (Amygdalifolia, Blaidy, Koronakei, Mary, Manzanillo, Mission, Rooghany, Valatolina, Wild olive, Zard) to the disease was assessed. Olive scab was found in all study areas and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…In both cases, under favorable conditions, sunken brown lesions may appear on petioles and fruits. Trees affected by olive leaf spots caused by V. oleaginea and P. cladosporioides show defoliation of leaves and weakness or death of branches, resulting in reduced fruit set and a decrease in oil yield in the following years [13,14,15,16,17,18]. These fungi survive in leaf lesions and spread through conidia, by rain, wind, or insects, which is the main source of inoculum for primary infection in spring [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…In both cases, under favorable conditions, sunken brown lesions may appear on petioles and fruits. Trees affected by olive leaf spots caused by V. oleaginea and P. cladosporioides show defoliation of leaves and weakness or death of branches, resulting in reduced fruit set and a decrease in oil yield in the following years [13,14,15,16,17,18]. These fungi survive in leaf lesions and spread through conidia, by rain, wind, or insects, which is the main source of inoculum for primary infection in spring [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The high levels of defoliation recorded in early spring confirmed that Moraiolo is a very susceptible cultivar to V. oleaginea ( Raggi and D'Armini, 1996 ). The importance of resistance/susceptibility of olive varieties to the pathogen in determining the level of attack is well known ( Agosteo and Schena, 2011 ; Sanei and Razavi, 2011 ; Rongai et al., 2012 ; Abuamsha et al., 2013 ; Buonaurio et al., 2023 ). The high levels of infections observed at the beginning of the experiments in symptomatic and asymptomatic leaves (15% + 50% = 65% of infected leaves) is due to the high susceptibility of the Moraiolo cultivar, the abundant rainfalls recorded in 2014 and 2015 and the orchard position which is located at the base of a hill where high relative air humidity occurs.…”
Section: Discussionmentioning
confidence: 99%
“…The high levels of infections observed at the beginning of the experiments in symptomatic and asymptomatic leaves (15% + 50% = 65% of infected leaves) is due to the high susceptibility of the Moraiolo cultivar, the abundant rainfalls recorded in 2014 and 2015 and the orchard position which is located at the base of a hill where high relative air humidity occurs. These are all factors known to promote fungal attack ( Obanor et al., 2008 ; Trapero and Blanco, 2010 ; Salman et al., 2011 ; Sanei and Razavi, 2011 ). The observed percentage of diseased leaves (65%) at the beginning of the trial is very high, considering that a value of 20% can be used as a threshold to execute treatments to keep the disease under control and keep the trees in a suitable physiological state ( Almadi et al., 2024 ).…”
Section: Discussionmentioning
confidence: 99%
“…cercospora leaf spot) [3]. Olive leaf spots caused by V. oleaginea and P. cladosporioides result in the defoliation of leaves and weakness or death of branches, a reduced fruit set, and a decrease in the oil yield in the following years [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%